Robotic right colectomy with complete mesocolic excision: Senior versus junior surgeon, a case‐matched retrospective analysis. Issue 3 (24th February 2022) - Ferraro, Luca; Formisano, Giampaolo; Salaj, Adelona; Giuratrabocchetta, Simona; Giuliani, Giuseppe; Salvischiani, Lucia; Bianchi, Paolo Pietro
Abstract: Background: Robotic surgery may facilitate complex procedures such as right colectomy with complete mesocolic excision (CME) and shorten the learning curve. This study aimed to compare senior and junior surgeons' results in performing robotic right colectomy (RRC) with CME and intracorporeal anastomosis for right colon cancer. Materials and Methods: Between January 2015 and April 2020, a total of 161 patients underwent RRC with CME. After propensity score matching, two groups of 31 patients for each surgeon were formed. Intraoperative, postoperative and pathological outcomes were the variables assessed. Results: No statistically significant difference was recorded between the two groups. The senior surgeon experienced 16.1% minor complications (Clavien–Dindo I‐II) and 3.2% major complications (Clavien–Dindo III‐IV), while the novice surgeon reported 19.3% and 3.2% rates of minor and major adverse events, respectively. Conclusions: After a structured training protocol, a novice may obtain comparable results to an expert in performing RRC with CME.